Pemodelan Logistik untuk Pertumbuhan Kependudukan Kabupaten Karo di Provinsi Sumatera Utara pada Tahun 2025-2026 - Latersia P, Egya Dora; Utami, Destia Nada; Amisri, Nurul Hasanah Tri; Hanafi, Muhammad Rizki (FARABI: Jurnal Matematika dan Pendidikan Matematika, 2025)
Population growth is the rate of change in the number of people living in an area at a given time compared to the number of people living in that area previously. Population changes have significant implications as they can influence the progress and welfare of a region. Population growth is one of the important factors that influence the social, economic, and environmental dynamics of a region. The prediction of population growth in Karo Regency aims to understand demographic dynamics and its implications for regional development. Karo Regency, located in North Sumatra, Indonesia, is experiencing a significant increase in population due to factors such as migration, births, and deaths. Based on data obtained from the Central Bureau of Statistics (BPS) of Karo Regency in 2020-2023, it can be assumed that the capacity (K) = 500,000. One alternative that can be used to forecast the population in Karo Regency is to utilize the logistic growth model. The results showed that the logistic model I with a relative growth rate per year of 7.26% so the results show that the population prediction of Karo Regency in 2025 is 425,385 and 2026 is 434,148.